Interaction of SIRT6 with telomeric chromatin in the context of ageing and cancer - Teh, Zhi Jing (Nanyang Technological University, 2024)
Sirtuin 6 (SIRT6) is a NAD+-dependent deacetylase with known functions in maintaining telomere integrity and cellular homeostasis. Early reports revealed the role of SIRT6 as a histone deacetylase while increasing studies have shown the protein’s involvement in regulating chromatin organisation. While recent Cryo-EM studies uncovered the structure of a SIRT6- mononucleosome complex, the mechanism dictating the function of SIRT6 in chromatin compaction remains uncertain. Here, we propose liquid-liquid phase separation (LLPS) as a potential mechanism constituting the ability of SIRT6 to regulate chromatin organisation. To discern the ability of SIRT6 in mediating telomeric chromatin LLPS, full-length SIRT6 and telomeric DNA were expressed in and purified using an E.coli system. The ability of SIRT6 to mediate telomeric chromatin LLPS is shown through the observation of droplet formation using confocal fluorescence microscopy with fluorescent-labelled histones. It was found that SIRT6 was capable of inducing phase separation in reconstituted telomeric nucleosome arrays. Interestingly, this LLPS behaviour was only observed beyond the specific stoichiometry of SIRT6:nucleosome ratio of 6. These droplets further demonstrated liquid-like properties with varying dynamicity depending on SIRT6 concentration. Collectively, these findings imply the unique function of SIRT6 as a telomeric chromatin-binding protein and its potential in ageing- related processes.